Analisis Kebijakan Pendidikan Islam dalam Undang-undang No. 20 Tahun 2003 (Sisdiknas) - Syafira Masnuah; Nyayu Khodijah; Ermis Suryana (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2022)
Islamic education is an educational concept that has existed in Indonesia for a long time even before Indonesia's independence. The birth of UU No. 20 of 2003 concerning ‘Sistem Pendidikan Nasional’ is the starting point for the development of Islamic education in Indonesia. This study uses a type of literature study (library research) to analyze Islamic education and UU in UU No. 20 of 2003 concerning ‘Sistem Pendidikan Nasional’. In the UU Sisdiknas No. 20 of 2003, Islamic education has been recognized for its existence in the national education system. This is indicated by the existence of several positions of Islamic education in UU No. 20 of 2003, that is (1) Islamic education as an educational institution both formal, non-formal, and informal that is explicitly recognized; (2) Islamic education as a material or subject of religious education as one of the subjects that must be given at the elementary to tertiary level; (3) Islamic education as the values ​​of Islamic teachings (value), namely when Islamic values ​​are found in the education system. However, in its implementation there are still problems that make the implementation of Islamic education less than optimal. So that in its implementation, the existence of Islamic education in UU No. 20 of 2003 (Sisdiknas) needs to be supported or elaborated in other regulations.